Knowledge, Patterns of Care, and Outcomes of Care for Generalists and Specialists - Harrold, Leslie R (Blackwell Science Inc, 1999)
OBJECTIVE: To critically evaluate the differences between generalist physicians and specialists in terms of knowledge, patterns of care, and clinical outcomes of care. METHODS: English-language articles (January 1981 to January 1998) were identified through a Medlinesearch and examination of bibliographies of identified articles. Systematic evaluation of articles relevant to adult medicine that had a direct comparison between generalist physicians and specialists in terms of knowledge relative to widely accepted standards of care, patterns of care (including use of medications, ancillary services, procedures, and resource utilization), and outcomes of care was performed. MAIN RESULTS: In many survey studies, specialists were reported to be more knowledgeable about conditions encompassed within their specialty. In terms of overall practice patterns, specialists practicing in their area of expertise were more likely to use medications associated with improved survival and to comply with routine health maintenance screening guidelines; they used more resources including diagnostic tests, procedures, and longer hospital stays. In the limited number of studies examining the care of patients with acute myocardial infarction, acute nonhemorrhagic stroke, and asthma, specialists had superior outcomes compared with generalists. CONCLUSIONS: There is evidence in the literature suggesting differences between specialists and generalists in terms of knowledge, patterns of care, and clinical outcomes of care for a broad range of diseases. In published studies, specialists were generally more knowledgeable about their area of expertise and quicker to adopt new and effective treatments than generalists. More research is needed to examine whether these patterns of care translate into superior outcomes for patients. Further work is also needed to delineate the components of care for which generalists and specialists should be responsible, in order to provide the highest quality of care to patients while most effectively utilizing existing physician manpower.